Analiz dinamiki i struktury dokhodnoi chasti biudzheta (na primere MO "Churapchinskii ulus (raion)") - Nikolaeva G. G. (Research dialogue: Finances and Credit)
The local budget acts as an important part of any municipality, because of the financial management efficiency depends most of the issues of life support of the population and its social stability . The paper analyzes the structure of the revenue side of the local budget by the example of the municipality " Churapchinsky District ( District) ."
Keywords: доходы; анализ; муниципальное образование; analysis; бюджет муниципального образования; the budget of the municipality; earnings; municipality Churapchinsky District ( District); Чурапчинский улус (район)